Scientific Understanding of Cytokine Storm in Perspective of Ayurveda: A Review (International Journal of Ayurveda and Pharma Research, 2022)
Cytokine storm also known as cytokine releasing syndrome is due to elevate level of circulating cytokine and hyper action that can be triggered by some factor like virus, bacteria or other epigenetic factors. In this era of communicable disease, COVID-19 is such a disease which shows manifestation in the form of cytokine storm. Increase level of cytokine like interleukin-6 etc in the blood causes destruction of normally functioning cell leads to dangerous life-threatening condition like ARDs. Cytokines are immunomodulating agents composed of soluble proteins, peptides and glycoproteins secreted by haemopoietic and non-haemopoietic cells in response to various stimuli. Their main role is in molecular interaction between various cells of the immune system. Cytokines are nothing but just the immune markers which hyperactivation leads to cytokine storm. There is not any description of such pathogenesis in Ayurveda. But Ayurveda clearly defined some concepts of immunity such Asvyadhikshamatva, Oja, Bala, Vyadhibighatakarabhaba and Rasayana. In Covid-19, researcher found that such people are more vulnerable to disease and its severity. Such vulnerability depends upon person response to illness. Ayurveda may explain this vulnerability through its concepts of preventive, personalized and rejuvenation. The present review focused on cytokine storm and its understanding in perspective of Ayurvedic concepts of immunity